IMPROVING STUDENTS’ SPEAKING SKILL THROUGH STORYTELLING TECHNIQUE (An Experimental Study in a Senior High School in Bandung) - Ratih Inayah (STKIP Siliwangi, 2015)
In senior high schools, the objective of the speaking skill is challenging, so it is not easy to achieve. The teachers and students may face some problems in the teaching and learning of speaking. Thus, this study attempts to investigate the effect of storytelling on students’ speaking ability and students’ attitudes toward its implementation of storytelling technique. This research was conducted at the tenth grade of a Senior High School in Bandung. It used a quasi-experimental design involving 30 students in the experimental group and in the control group respectively. The experimental group was given the treatment with storytelling technique, while the control group with conventional technique. The instruments used were speaking test (pre-test and post-test) given to both groups, and questionnaires to the experimental group only. The result of this study shows that : 1) the storytelling technique had an effect on improving students’ speaking ability because there was a significant difference between the post-test scores of students in experimental and control groups with the level of significance 0f 0,05 the t-observed (2,106) was higher than t-table (1,684). 2) Overall, students’ attitudes toward the implementation of storytelling technique were positive because they enjoyed the learning process and they were interested in the story. Moreover, the storytelling technique could help them to improve their speaking ability.Keywords: Speaking ability, Storytelling, Technique.